MON-628 Noninvasive Encapsulated Papillary RAS-Like Thyroid Tumor (NEPRAS) as a Possible Novel Subtype of Borderline Tumor - Ohba, Kenji (J Endocr Soc, 2019)
Background: A subset of thyroid tumors was classified into borderline/precursor tumors in the latest World Health Organization (WHO) classification. However, these tumors were defined only in terms of follicular structure, including hyalinizing trabecular tumor (HTT), noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP), and uncertain malignant potential (UMP). As papillary microcarcinoma was proposed to be renamed to papillary microtumor (PMiT), there would be no reasons for restricting borderline/precursor tumors to the follicular growth pattern. Clinical Case: A 26-year-old man was incidentally found to have a 23 mm nodule in his thyroid. After undergoing left lobectomy, histological findings revealed extremely delicate nuclear changes in a noninvasive encapsulated papillary growth-patterned tumor. Tumor cells showed nuclear enlargement, irregularity, elongation, and overlapping as well as a few nuclear grooves. Nuclear pseudoinclusions were absent and chromatin characteristics were insufficient (nuclear score 2 according to Nikiforov et al. (1)). The patient was diagnosed with an encapsulated conventional papillary thyroid carcinoma by a local pathologist; however, a second-opinion consultation endorsed a follicular adenoma with papillary hyperplasia. In a third-opinion consultation, immunohistochemical analyses revealed a low MIB-1 labeling index and negative staining for cytokeratin 19 and BRAFV600E, which supported the expected indolent clinical behavior. Remarkably, mutational analysis identified a heterozygous point mutation of the KRAS gene but not the BRAF genes. Eventually, we speculated that this tumor could be a possible example of a novel borderline tumor with a papillary architecture, which does not qualify as NIFTP or UMP under the current WHO criteria. The patient refused additional surgery (complete thyroidectomy), and developed no recurrence or distant metastasis for 24 months. Conclusion: We reported a significant observer variation in a noninvasive encapsulated papillary growth-patterned tumor with delicate nuclear changes and a KRAS mutation. We speculated that our case could be an example of a novel borderline tumor with a papillary structure. Further studies using a larger number of patients are needed to elucidate this disease entity, because the possible introduction of terminology such as “noninvasive encapsulated papillary RAS-like thyroid tumor (NEPRAS)” without the word “cancer” could relieve psychological burdens of the patients similar to NIFTP. Reference: (1) Nikiforov YE, et al. Nomenclature Revision for Encapsulated Follicular Variant of Papillary Thyroid Carcinoma: A Paradigm Shift to Reduce Overtreatment of Indolent Tumors. JAMA Oncol. 2016;2:1023-9.